PEAR MATHEMATICAL MODEL ON ONLINE GAME ADDICTION - Damani, Nur Mila; Patty, Henry W. M.; Lesnussa, Yopi Andry (Jurnal Sains Dasar, 2024)
Online game addiction is a mental disorder seen from the urge to play online games to forget time and even ignore other activities and responsibilities such as work and school assignments. This research discusses the PEAR mathematical model of online game addiction. This research aims to construct, analyze the equilibrium point and simulate the PEAR model of online game addiction. From the research results, the construction of the PEAR mathematical model has been obtained. The results of the equilibrium point analysis and stability found two equilibrium points, namely the addiction-free equilibrium point and the endemic equilibrium point. Based on the results of analysis and numerical simulation of the PEAR mathematical model of online game addiction using Python software, it is obtained that the Potential sub-population has decreased in the 5th month, the Exposed sub-population decreased in the 10th month, the Recovered sub-population has increased individuals from the Exposed sub-population so that there is an increase in individuals until the 2nd month. However, there was a decreased number of individuals until the 10th month, and all Addicted sub-populations entered the Recovered sub-population in the 12th month, so this sub-population has increased